Combination of the transurethral resection and prostate HIFU ablation at treatment of the localized cancer - Popkov V.M.; Fomkin R.N.; Blyumberg B.l.; Shatylko T.V.; Sedova L.N.; Abramova E.P. (Саратовский научно-медицинский журнал, 2014)
Research objective: to estimate results of treatment of patients with the localized form of a cancer of a prostate at a combination of a transurethral resection (TURP) and HIFU of an ablation. Objects and research methods: From February, 2009 to February, 2014 of 100 patients with the localized form of a cancer of a prostate were selected for research: 26 patients were included into HIFU and 74 group in group of the combined treatment (TURP+HIFU). Selection criteria for HIFU ablation were the localized cancer of a prostate concerning which earlier it wasn't carried out treatments, and level of a PSA at the time of statement of the diagnosis 15 ng/ml. All patients corresponding to these by criteria, were considered as candidates for treatment and inclusion in the analysis. The nadir and stability of PSA, the histologic conclusion, IPSS, quality of life and complication were estimated at time of postoperative supervision. Results: Statistically significant influence of a combination TURP+HIFU for the term of transurethral drainage of a bladder (a median of 40 days against 7 days), incontience frequency (15.4% against 6.9%), infections of urinary ways (47.9% against 11.4%) and IPSS change during the postoperative period (on the average 8.91 against 3.37) is noted. During the short period of supervision it wasn't observed considerable changes in relation to efficiency: in HIFU group the frequency of repeated sessions made 25%, in TUR/HIFU group 4%. Conclusion: HIFU therapy is modern, minimum invasive method of a cancer therapy of a prostate. The combination of a transurethral resection and HIFU ablation significantly reduces the frequency of the complications connected with treatment. Maintaining the patient after combined TURP and HIFU ablation is comparable with maintaining the patient after usual TURP.